Kompetensi Komunikasi Mahasiswa Dalam Proses Penyelesaian Tugas Akhir - Adrian, Yulia; Hariyati, Farida; Nurhadi, Zikri Fachrul (Jurnal Komunikasi Universitas Garut: Hasil Pemikiran dan Penelitian, 2023)
Communication has a very important role in human life, one of which is interpersonal communication. For final year students, interpersonal communication with the supervisor becomes important as an interactive process of exchanging the meaning of messages in order to produce an explanation for the research that is being carried out by students. In line with the purpose of this research, it is to find out whether the communication competence possessed by students during college supports the process of working on the thesis properly and completely. In order to know the purpose of the study, the researcher used qualitative research methods in order to be able to construct the subject's statement so that the arguments from the results of this study were relevant to the competence of final year students in the process of completing the final project. After conducting in-depth observations and interviews based on the background of the problem and theory in this study, the researcher constructed the answers from the informants regarding the motivation, skills, and knowledge possessed by students during college and the contribution of these three things in the process of completing the final project. The results of the research based on the theory of communication competence explain that oneself is the main impetus in working on the thesis and other encouragement such as parents, spouse, and friends who accompany it. With the encouragement factor, it can be concluded that in the process of completing the final project, University Muhammadiyah Prof. Dr. Hamka final year students have good communication competence. Thus, this study confirms that communication competence is an important thing for final year students in the process of working on and completing the final project.